The Horror of Police - Linnemann, Travis (University of Minnesota Press, 2022)
"Drawing on the language and texts of horror fiction, Travis Linnemann recasts the police not only as self-proclaimed "monster fighters" but as monsters themselves, a terrifying force set loose in the world. The Horror of Police shows that police violence is not a deviation but rather a deliberate and permanent fixture of U.S. "law and order.""--